Guest Editorial: Environmental Information System - Singh, Harjit (DESIDOC Journal of Library & Information Technology, 2003)
Today,degradation of environment has become a serious problem all over the world.Various countries are now concerned with the adverseconseequences of destruction of their natural resources problems like unusual weather,floods,drought,ozone depletion and glass house -effect are being attributed to pollution in air and water combined with mismanagement of solid waste and spread of other pollutants. http://dx.doi.org/10.14429/dbit.19.2.3464